2017
DOI: 10.1149/2.1351714jes
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Growth of Electrochemically Formed Iridium Oxide Films

Abstract: The nature of the electronic structure of electrochemically formed iridium oxide films (EIROF) is investigated by in-situ conductivity measurements in an electrochemical cell and ex-situ current-sensing atomic force microscopy (CS-AFM). A direct demonstration of changes in the conductivity for electrochemically formed iridium oxide films (EIROF) with the applied potential of EIROF electrodes in an electrochemical cell is presented. The in-situ conductivity shows a single step-like change at a potential of appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The electronic structure of AIROF appears to be that of a semiconductor in the reduced state (reaction (2) shifted to the right) and conducting in the oxidised (reaction (2) shifted to the left) 27,58 . A direct measurement of this transition from in-situ conductivtiy and scanning-probe measurements was reported by Ilyukhina et al 26 for electrochemically formed iridium oxide (EIROF). The H-UPD region would appear at potentials at which the oxide is reduced and thus semiconducting.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The electronic structure of AIROF appears to be that of a semiconductor in the reduced state (reaction (2) shifted to the right) and conducting in the oxidised (reaction (2) shifted to the left) 27,58 . A direct measurement of this transition from in-situ conductivtiy and scanning-probe measurements was reported by Ilyukhina et al 26 for electrochemically formed iridium oxide (EIROF). The H-UPD region would appear at potentials at which the oxide is reduced and thus semiconducting.…”
Section: Discussionmentioning
confidence: 88%
“…In some cases the oxides are electrochromic, i.e. their color changes with the state of charge (sputtered iridium oxides (SIROF) 23 , AIROF 24,25 , and electrochemically deposited iridium oxide (EIROF) 26 ), in others not (hydrolysis) 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The electronic conductivity of IrO x , which is the most commonly used anode, electrocatalyst highly depends on anodic potential which affects its oxidation state. It has been shown that electrochemically deposited iridium oxide film behaves as a p-type semiconductor at small anodic potentials, but transitions to metallic behaviour for potentials higher than 1.2 V. 102 Although the intrinsic electronic conductivity of IrO x is high enough, the conductivity of the CL is determined by its ionomer content and the structure and percolation level of IrO x particles in the CL.…”
Section: Ptl/cl Interfacementioning
confidence: 99%
“…This trend matches with the a constant to slightly increasing conductivity at low-potentials and a stronger increase at a potential of about 1.20 VRHE observed earlier by the group of Haverkamp. 25 The assumption that the changes in the ellipsometric spectra are caused by changes in resistivity has to be validated. Therefore, operando ECSE measurements were performed on a non-conductive mesoporous titanium oxide (TiOx) film in the OER regime and in the potential range between 0.40 VRHE and 1.40 VRHE.…”
Section: Ecse Investigation Of a Mesoporous Irox Film Calcined At 375 °Cmentioning
confidence: 99%